(untitled) (Journal of Fiber Bioengineering and Informatics, 2021)
We examined the relationship between ease of pyjamas and body on the thermal insulation of men's pyjamas made from a knitted fabric of a new cotton-based non-twisted hollow yarn to obtain design guidelines for higher heat retention. We made six sets of men's pyjamas that have different ease for the circumferences of chest, hip, and sleeve. We measured the heating power required for different parts of a thermal manikin to remain at a constant temperature when the manikin wore the pyjamas. We also measured the thermal insulation when the cuffs of the upper garment and the hems of the lower garment were closed with belts. To evaluate the effect of ease of wearing state on thermal insulation quantitatively, the differences of circumference and area of the cross-section between thermal manikin and a pyjama worn on the manikin were calculated from those 3D scanned data. We investigated the relationship between the heating power and the differences. As a result, the heat retention increased as the differences increased although there are variations depending on the location. There was almost no effect of convection from the cuffs and hems in the experimental environment without wind.